Chronic Physical Disorders 2002
DOI: 10.1002/9780470693513.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Heart Disease

Abstract: Background-The effect of β-blockers on infarct size when used in conjunction with primary percutaneous coronary intervention is unknown. We hypothesize that metoprolol reduces infarct size when administered early (intravenously before reperfusion). Methods and Results-Patients with Killip class II or less anterior ST-segment-elevation myocardial infarction (STEMI)undergoing percutaneous coronary intervention within 6 hours of symptoms onset were randomized to receive intravenous metoprolol (n=131) or not (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 193 publications
0
2
0
Order By: Relevance
“…T. Smith & Ruiz, 2002;Sullivan, et al, 1999). A number of studies support the notion of a gradient between the magnitude of depression and future cardiac events, suggesting that risk for coronary artery disease associated with depression exists along a continuum, with the relative risk depending on the magnitude of depressive symptoms (Glassman & Shapiro, 1998;Rozanski, et al, 1999).…”
Section: Cardiovascular Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…T. Smith & Ruiz, 2002;Sullivan, et al, 1999). A number of studies support the notion of a gradient between the magnitude of depression and future cardiac events, suggesting that risk for coronary artery disease associated with depression exists along a continuum, with the relative risk depending on the magnitude of depressive symptoms (Glassman & Shapiro, 1998;Rozanski, et al, 1999).…”
Section: Cardiovascular Diseasementioning
confidence: 97%
“…One study found an increased risk for cardiac mortality or MI among 72% of its participants reporting only two symptoms of depression, a level of depression insufficient to diagnose major or even minor depression (Horsten, Mittleman, Wamala, Schenck-Gustafsson, & Orth-Gomér, 2000). Among those who have suffered a heart attack higher levels of depression or anxiety is associated with increased mortality and morbidity, poor emotional recovery, lack of short term improvement, and longer latency to normal levels of activity (P. Bennett & Carroll, 1997;Gorkin, Follick, Wilkin, & Niaura, 1994;Pratt, et al, 1996;T. Smith & Ruiz, 2002).…”
Section: Cardiovascular Diseasementioning
confidence: 99%